Voxel-based meta-analysis of gray matter and white matter changes in patients with spinocerebellar ataxia type 3 - Liu, Hai; Lin, Junyu; Shang, Huifang (Frontiers in Neurology, 2023)
Purpose Increasing neuroimaging studies have revealed gray matter (GM) and white matter (WM) anomalies of several brain regions by voxel-based morphometry (VBM) studies on patients with spinocerebellar ataxia type 3 (SCA3); however, the findings of previous studies on SCA3 patients by VBM studies remain inconsistent. The study aimed to identify consistent findings of gray matter (GM) and white matter (WM) changes in SCA3 patients by voxel-wise meta-analysis of whole-brain VBM studies. Methods VBM studies comparing GM or WM changes in SCA3 patients and healthy controls (HCs) were retrieved from PubMed, Embase, Web of Science, and Medline databases from January 1990 to February 2023. Manual searches were also conducted, and authors of studies were contacted for additional data. The coordinates with significant differences in GM and WM between SCA3 patients and HCs were extracted from each cluster. A meta-analysis was performed using anisotropic effect size-based signed differential mapping (AES-SDM) software. Results A total of seven studies comprising 160 SCA3 patients and 165 HCs were included in the GM volume meta-analysis. Three studies comprising 57 SCA3 patients and 63 HCs were included for WM volume meta-analysis. Compared with HC subjects, the reduced GM volume in SCA3 patients was found in the bilateral cerebellar hemispheres, cerebellar vermis, pons, right lingual gyrus, and right fusiform gyrus. The decreased WM volume was mainly concentrated in the bilateral cerebellar hemispheres, right corticospinal tract, middle cerebellar peduncles, cerebellar vermis, and left lingual gyrus. No increased density or volume of any brain structures was found. In the jackknife sensitivity analysis, the results remained largely robust. Conclusion Our meta-analysis clearly found the shrinkage of GM and WM volume in patients with SCA3. These lesions are involved in ataxia symptoms, abnormal eye movements, visual impairment, cognitive impairment, and affective disorders. The findings can explain the clinical manifestations and provide a morphological basis for SCA3.